Psychological Mechanisms that Affect Economic Decisions to Work Longer - Topa, Gabriela; Earl, Joanne; Boone James, Jacquelyn (Frontiers Media SA, 2020)
Progressive aging of the Baby Boomer generation, early workplace withdrawals and international trends towards longevity place increasing pressure on governments to provide economic solutions. One possibility involves promoting financial self-sufficiency and shifting responsibility from governments back to individuals. This involves, in part, promoting the abolishment of mandatory retirement ages and devising strategies to keep people at work for longer. At an individual level choosing how and when to transition can deliver psychological benefits while continuing to work provides opportunities to remain socially and intellectually connected. There are also obvious economic benefits for disadvantaged groups such as women, immigrants and less qualified workers who may be ill equipped to retire comfortably. When combined these sufficiently motivate the pursuit of solutions that overcome constraints and encourage later life employment. There are, however, two sets of competing demands, namely balancing the desire and economic demand to work longer within current contemporary workplace designs and the cognitive, physical and psychological capacities of workers to fulfill these demands indefinitely. The study of the psychological mechanisms that underlie economic behavior may increase our understanding of how bridge employment opportunities, flexible work schedules, training to move to new careers, and starting new business and franchisees might result in higher proportions of older workers remaining in the labor market. Such an approach is expected to lead to a better understanding of employer attitudes and responses to older workers with innovative workplace and human factors that encourage more years of labor force participation.